Possible Waardenburg syndrome with gastrointestinal anomalies. Issue 2 (April 1986) - Nutman, J; Steinherz, R; Sivan, Y; Goodman, R M
Abstract : We describe a patient with possible Waardenburg syndrome associated with anal atresia and oesophageal atresia with tracheooesophageal fistula. Three other published cases with atretic gastrointestinal anomalies associated with the Waardenburg syndrome are reviewed. We conclude that the association between atretic lesions of the gastrointestinal tract and the Waardenburg syndrome may be a significant one.